Geographical targeting to improve progression through the sexually transmitted infection/HIV treatment continua in different populations. Issue 6 (November 2015) - Aral, Sevgi O.; Torrone, Elizabeth; Bernstein, Kyle
Abstract : Purpose of review: The purpose of this study is to review and synthesize the recent literature on the use of geographical targeting to improve progression through HIV and sexually transmitted disease (STD) prevention and treatment continua in different populations. Recent findings: Geographical targeting can help identify obstacles to progression through prevention and treatment continua for each stage and in specific geographic locations. Macro-level geographical targeting can help maximize allocative efficiency, while micro-level targeting of hot spots increases effectiveness of interventions. Migration into and out of geographical areas of interest constitutes a challenge to geographical targeting in that stage-specific monitoring strategies tend to yield inaccurate results when people leave the area. Despite these issues, it is possible to identify failures in each stage of the continuum by specific spatial location such as census tracts and focus improvement efforts accordingly. Summary: Vulnerabilities, risk behaviours and infections all cluster across age, race-ethnicity, socioeconomic status, key populations, risk networks and geographic space. Spatial concentration may be the most important in this context, as it allows prevention programmes to identify and reach target populations more easily. Geographical targeting can be employed at both macro and micro levels and in combination with targeting of key populations and high-risk networks.